American diplomacy - Sharp, Paul, 1953-; Wiseman, Geoffrey (Martinus Nijhoff Publishers, 2012)
This volume discusses how diplomacy's contribution to the effectiveness of foreign policy has been undervalued in the United States by governments, the foreign policy community, and academics. Chapters raise awareness of the importance of American diplomacy, what it can and can't achieve, and how it may be strengthened in the interests of international peace and security.